Letter from Henry M. Morfit to James Curtis Booth, November 20, 1859 - Morfit, Henry Mason (1859)
Henry M. Morfit (1793-1865) asks questions about the commercial value of cobalt ore. Morfit, a claims lawyer in Washington, D.C. and a political figure in the Andrew Jackson presidential administrations, appears to have served as go-between for his son, Campbell Morfit (1820-1897), and James Curtis Booth (1810-1888) in their efforts to interest the U.S. Mint in their process for refining gold.
Keywords: United States Mint; Mint of the United States; Booth, James Curtis, 1810-1888; Metals--Refining; United States. Assay Office, New York City; Morfit, Campbell, 1820-1897; Cobalt